Observation and polarization measurement of B-0 -> a(1)(1260)(+)a(1)(1260)(-) decay - Aubert, B; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Tico, J; Grauges, E; Martinelli, M; Palano, A; Pappagallo, M; et al. (2009)
We present measurements of the branching fraction B and longitudinal polarization fraction fL for B0→a1(1260)+a1(1260)- decays, with a1(1260)±→π-π+π±. The data sample, collected with the BABAR detector at the SLAC National Accelerator Laboratory, represents 465×106 produced BB̄ pairs. We measure B(B0→a1(1260)+a1(1260)-) ×[B(a1(1260)+→π-π+π+)]2=(11.8±2.6±1.6) ×10-6 and fL=0.31±0.22±0.10, where the first uncertainty is statistical and the second systematic. The decay mode is measured with a significance of 5.0 standard deviations including systematic uncertainties. © 2009 The American Physical Society.